1999
DOI: 10.1177/0095798499025002004
|View full text |Cite
|
Sign up to set email alerts
|

Statistics Anxiety among African American Graduate Students: An Affective Filter?

Abstract: The recruitment and retention of African Americans in graduate schools remains a significant problem. Statistics anxiety has been found to be prevalent among graduate students, being implicated both as a barrier to success in quantitative courses and a barrier to completion of theses and dissertations. To date, it is unclear whether African American graduate students experience higher levels of statistics anxiety. Thus, the purpose of this study was to compare levels of statistics anxiety between African Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
4
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 36 publications
4
50
4
9
Order By: Relevance
“…Onwuegbuzie et al (1999) believe that language learning anxiety can influence their learning in general and their fluency of speech in particular. Similarly, Kondo and Ling (2004) hold the view that learners who feel anxious may have problems such as reduced word production and difficulty in understanding spoken instructions.…”
Section: Cause and Effect Of Anxietymentioning
confidence: 99%
“…Onwuegbuzie et al (1999) believe that language learning anxiety can influence their learning in general and their fluency of speech in particular. Similarly, Kondo and Ling (2004) hold the view that learners who feel anxious may have problems such as reduced word production and difficulty in understanding spoken instructions.…”
Section: Cause and Effect Of Anxietymentioning
confidence: 99%
“…Onwuegbuzie (1999) estimated that approximately 75% of students experience moderate to high levels of statistics anxiety. Therefore, it may be an obstacle to undergraduate and graduate students (Onwuegbuzie & Wilson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Bell (2003) and Onwuegbuzie (1999) found that older students experienced more statistics anxiety than their younger counterparts. Baloğlu (2003) found that age had a significant multivariate effect on the components of statistics anxiety in that older students showed higher levels of statistics anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to Caucasian students, female African American social work students scored higher on a scale of statistics anxiety (Davis, 2003), and a sample of predominantly female African American Department of Education students scored higher levels of statistics-related anxiety and test anxiety compared to their Caucasian counterparts (Onwuegbuzie, 1999). Among many factors, statistics-related anxiety has been identified as an obstacle to academic success among African American BSW students.…”
Section: Explore Importance Of the Problemmentioning
confidence: 98%